Cardiovascular and renal diseases in type 2 diabetes patients: 5-year cumulative incidence of the first occurred manifestation and hospitalization cost: a cohort within the French SNDS nationwide claims database - Patrick Blin; Michael Joubert; Patrick Jourdain; Philippe Zaoui; Estelle Guiard; Dunia Sakr; Caroline Dureau-Pournin; Marie-Agnès Bernard; Régis Lassalle; Florence Thomas-Delecourt; Sébastien Bineau; Nicholas Moore; et al. (Cardiovascular Diabetology, 2024)
Abstract Background Myocardial infarction (MI), stroke, peripheral arterial disease (PAD), heart failure (HF) and chronic kidney disease (CKD) are common cardiovascular renal diseases (CVRD) manifestations for type 2 diabetes. The objective was to estimate the incidence of the first occurring CVRD manifestation and cumulative hospitalization costs of each CVRD manifestation for type 2 diabetes without CVRD history. Methods A cohort study of all type 2 diabetes free of CVRD as of January 1st 2014, was identified and followed-up for 5 years within the French SNDS nationwide claims database. The cumulative incidence of the first occurring CVRD manifestation was estimated using the cumulative incidence function, with death as a competing risk. Cumulative hospitalization costs of each CVRD manifestations were estimated from the perspective of all payers. Results From 2,079,089 type 2 diabetes without cancer or transplantation, 76.5% were free of CVRD at baseline with a mean age of 65 years, 52% of women and 7% with microvascular complications history. The cumulative incidence of a first CVRD manifestation was 15.3% after 5 years of follow-up with a constant linear increase over time for all CVRD manifestations: The most frequent was CKD representing 40.6% of first occurred CVRD manifestation, followed by HF (23.0%), then PAD (13.5%), stroke (13.2%) and MI (9.7%). HF and CKD together reached about one patient out of ten after 5 years and represented 63.6% of first CVRD manifestations. The 5-year global cost of all CVRD hospitalizations was 3.9 billion euros (B€), i.e. 2,450€ per patient of the whole cohort, with an exponential increase over time for each specific CVRD manifestation. The costliest was CKD (2.0 B€), followed by HF (1.2 B€), then PAD (0.7 B€), stroke (0.6 B€) and MI (0.3 B€). Conclusions/interpretation While MI, stroke and PAD remain classic major risks of complications for CVRD-free type 2 diabetes, HF and CKD nowadays represent individually a higher risk and cost than each of these classic manifestations, and jointly represents a risk and a cost twice as high as these three classic manifestations all together. This should encourage the development of specific HF and CKD preventive strategies.